Porites randalli: a new coral species (Scleractinia, Poritidae) from American Samoa - Forsman, Zac H.; Birkeland, Charles (Zootaxa, 2009)
A new species of scleractinian coral, Porites randalli spec. nov. (Scleractinia, Poritidae), previously known as Porites sp. 2, is described from American Samoa. P. randalli typically forms small pale green colonies that are usually Porites randalli spec. nov. is an example of cryptic diversity; it is a small coral that at first glance can be overlooked or mistaken for a young colony of other species.